2016
DOI: 10.1371/journal.pone.0157711
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Detection of CNVs and Their Association with Meat Tenderness in Nelore Cattle

Abstract: Brazil is one of the largest beef producers and exporters in the world with the Nelore breed representing the vast majority of Brazilian cattle (Bos taurus indicus). Despite the great adaptability of the Nelore breed to tropical climate, meat tenderness (MT) remains to be improved. Several factors including genetic composition can influence MT. In this article, we report a genome-wide analysis of copy number variation (CNV) inferred from Illumina® High Density SNP-chip data for a Nelore population of 723 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 120 publications
(143 reference statements)
7
54
2
5
Order By: Relevance
“…Seventy two percent of the CNVs were identified, which were marked by flanking SNPs as reported by Xu et al [8] . However, the results of this investigation were not efficiently capable to distinguish recent divergent populations of common geographic origin, such as Cholistani and Bhagnari cattle breeds and also reported by Silva et al [7] and Xu et al [8] in Holstein and Angus cattle breeds. Human published data also revealed that the CNVs based on population genetic properties can only be investigated with large data set of continent population level [10] .…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Seventy two percent of the CNVs were identified, which were marked by flanking SNPs as reported by Xu et al [8] . However, the results of this investigation were not efficiently capable to distinguish recent divergent populations of common geographic origin, such as Cholistani and Bhagnari cattle breeds and also reported by Silva et al [7] and Xu et al [8] in Holstein and Angus cattle breeds. Human published data also revealed that the CNVs based on population genetic properties can only be investigated with large data set of continent population level [10] .…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies in some species, including Human, Dog, Zebra fish, Stickleback fish and some worldwide cattle breeds have identified CNVs, based on population genetic properties, within and between population [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works of , Ben Sassi et al (2016), Jiang et al (2016) and Upadhyay et al (2017), CNVs were significantly associated with milk production traits. In addition, CNVs of the genes are associated with reproduction and milk phenotype in cattle (Durán Aguilar et al, 2017;Da Silva et al, 2016b;McCarthy et al, 2012;Prinsen et al, 2017;Sermyagin et al, 2016;Shin et al, 2014;Xu et al, 2016;Yue et al, 2013;Zhou et al, 2018). In chickens, novel CNV of the TGFβ3 gene is associated with duration of fertility traits (Gu et al, 2017).…”
Section: Association Of Cnvs With Reproduction and Production Traitsmentioning
confidence: 99%
“…Such regions are denoted as CNV calls and are the starting point for subsequent downstream analysis. In previous work, we developed, described, and applied functionality for analyzing CNVs across a population, including association analysis with gene expression and quantitative phenotypes (da Silva et al, 2016(da Silva et al, , 2018Geistlinger et al, 2018). To allow straightforward application to similar datasets, we generalize these concepts and provide refined implementations in the CNVRanger R/Bioconductor package.…”
Section: Introductionmentioning
confidence: 99%